Is It Appropriate to Implement the Accounting Treatment for Production Employee Benefits at PT XYZ? - Audina Safira Yunita; Retno Widiastuti; Yusna (Politeknik Negeri Malang, 2023)
The purpose of this research was to evaluate the suitability of the employee benefits accounting treatment. Accounting treatment includes recognition, measurement, presentation, and disclosure for production employees at PT XYZ with SAK ETAP Chapter 23. This research type is descriptive quantitative. Research methods that used to collect the data are interviews and documentation to obtain the secondary data sources. The results showed that PT XYZ has already implemented the accounting treatment of employee benefits for its production division employees as required in SAK ETAP Chapter 23. However, the company only applies 3 types of employee benefits which are short-term employee benefits, post-employment benefits, and other long-term benefits, whereas for employee benefits type termination benefits have not been implemented by the company.